Multinational Marketing Management / Cases and Readings - Buzzell Robert D; Quelch John A (1988)
The contents of this book are based on the highly acclaimed Harvard Business School executive seminar on multinational marketing. Designing Strategies for Multinational Competition, Multinational Marketing Programs, Organizing and Controlling Multinational Operations, Selected Bibliography.